(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article studies the essence, role and significance of regional marketing in the socio-economic development of the region. The results of the theoretical analysis of the essence of the concept of "regional marketing" are given. Based on the results of the analysis, a model of the mechanism for the implementation of regional marketing has been developed.